Comparison of birth weight, length, and head circumference between the BRISA-RP and Intergrowth-21st cohorts - João Roberto R. Pimenta; Carlos Grandi; Davi C. Aragon; Viviane Cunha Cardoso (Elsevier, 2020)
Objectives: (a) To determine the 3rd, 50th, and 97th percentiles of weight, length, and head circumference of newborns from the Ribeirão Preto BRISA cohort, according to gender and gestational age, and compare them with the Intergrowth-21st standard; (b) To estimate the small for gestational age ( < 3rd percentile), large for gestational age ( > 97th percentile), stunting (length < 3rd percentile), and wasting (body mass index < 3rd percentile). Methods: Observational study of a cohort of 7702 newborns between 01/01/2010 and 12/31/2010 in the city of Ribeirão Preto, SP, Brazil. The 3rd, 50th, and 97th percentiles were determined for the anthropometric measurements using fractional polynomial regression. Results: The weight difference between Ribeirão Preto and Intergrowth-21st was small, being more pronounced in preterm infants (mean difference between the two populations of +266 g); for full-term newborns, there was a mean difference of +66 g, and for post-term infants, of −113 g. For length, the mean variation was always <1 cm; whereas for head circumference, preterm newborns showed a variation >1 cm, and full-term and post-term newborns showed a variation of <1 cm. The small and large for gestational age detection rates were 2.9% and 4.3%, respectively. Stunting affected 6.5% of all newborns and wasting, 1.5%, with a predominance in girls and in full-term pregnancies; both conditions were present in 0.4% of the sample. Conclusions: Newborns from Ribeirão Preto, when compared to the Intergrowth-21 standard, are heavier, longer, and have a larger head circumference until they reach full-term. Resumo: Objetivos: Determinar os percentis 3, 50 e 97 de peso, comprimento e perímetro cefálico de recém-nascidos da Coorte BRISA Ribeirão Preto, segundo sexo e idade gestacional, e comparar com o padrão Intergrowth-21st; b) Estimar os fenótipos pequeno para idade gestacional ( < percentil 3), grande para idade gestacional ( > percentil 97), stunting (comprimento < percentil 3) e waisting (índice de massa corporal < percentil 3). Método: Estudo observacional de uma coorte de 7.702 recém-nascidos entre 01/01 e 31/12/2010 na cidade de Ribeirão Preto, SP, Brasil. Os percentis 3, 50 e 97 para as medidas antropométricas foram determinados com regressão polinomial fracionária. Resultados: A diferença de peso entre Ribeirão Preto e Intergrowth-21st foi pequena, mais acentuada nos recém-nascidos pré-termo (diferença média entre as duas populações foi de + 266 gramas); para os recém-nascidos a termo a diferença média foi de + 66 gramas e para os pós-termo de -113 gramas. Para comprimento, a variação média foi sempre < 1 cm; enquanto que para perímetro cefálico os recém-nascidos pré-termo apresentaram variação > 1 cm e os recém-nascidos a termo e pós-termo tiveram variação < 1 cm. As taxas de detecção de pequeno e grande para idade gestacional foram 2,9% e 4,3%, respectivamente. Stunting afetou 6,5% de todos os recém-nascidos e waisting 1,5%, com predomínio em meninas e em gestações a termo; ambas as condições estavam presentes em 0,4% da amostra. Conclusões: Os recém-nascidos de Ribeirão Preto, quando comparados com o padrão Intergrowth-21st, apresentam-se mais pesados, mais longos e com maior circunferência craniana até chegarem a termo.